Synthesis of CuO/Zn₂SnO₄ Nanocomposites via Hydrothermal Method and Their Photocatalytic Performance for Ciprofloxacin Degradation - Rika Agustin; Vivi Sisca; Asdim Asdim; Eka Angasa (Jurnal Kimia Sains dan Aplikasi, 2025)
CuO/Zn2SnO4 nanocomposites were successfully synthesized via a hydrothermal method at 180°C for 5 hours. The CuO/Zn2SnO4 nanocomposites were developed to evaluate their potential as photocatalysts for the degradation of ciprofloxacin, a pharmaceutical pollutant commonly found in water sources. The materials were characterized using XRD, SEM, TEM, and UV-Vis DRS analyses. XRD results confirmed that the CuO/Zn2SnO4 nanocomposites, prepared with various CuO concentrations (20, 40, 60, and 80% w/w), exhibited good crystallinity and high purity. SEM analysis revealed that the morphology of the composites consisted of square-shaped nanosheets resembling CuO and irregular, round particles with non-uniform sizes resembling Zn2SnO4. TEM analysis further confirmed that the CuO/Zn2SnO4 nanocomposite with 40% CuO exhibited irregular square and round nanosheets with an average size of 69.53 nm. UV-Vis DRS analysis showed that the band gap of pure Zn2SnO4 (3.22 eV) decreased after the incorporation of CuO, with values of 1.67 eV (20%), 1.46 eV (40%), 1.50 eV (60%), and 1.50 eV (80%). The photocatalytic activity of the nanocomposites was evaluated based on the degradation of ciprofloxacin under sunlight irradiation. The degradation percentages of pure Zn2SnO4, pure CuO, and CuO/Zn2SnO4 with 20% CuO were 78.3%, 8.9%, and 47.1%, respectively. This study demonstrates that the CuO/Zn2SnO4 nanocomposite has fewer active surface sites than pure Zn2SnO4, which significantly influences its photocatalytic performance.